2011
DOI: 10.3402/gha.v4i0.7226
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic obstructive pulmonary disease in rural women of Tamilnadu: implications for refining disease burden assessments attributable to household biomass combustion

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is the 13th leading cause of burden of disease worldwide and is expected to become 5th by 2020. Biomass fuel combustion significantly contributes to COPD, although smoking is recognized as the most important risk factor. Rural women in developing countries bear the largest share of this burden resulting from chronic exposures to biomass fuel smoke. Although there is considerable strength of evidence for the association between COPD and biomass smoke exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 23 publications
3
47
9
Order By: Relevance
“…In Latin America and Asia, studies have found an association of exposure to solid fuel smoke with COPD and chronic bronchitis, especially in women. 1,[17][18][19][20][21] In Sub-Saharan Africa, a study conducted by Fullerton in Malawi reported a COPD prevalence of 16%, higher than this study (1.6% among wood users). 10 The difference in results may be explained by the fact that the Malawian study included men and women whereas our study population comprised only women.…”
Section: Discussioncontrasting
confidence: 75%
“…In Latin America and Asia, studies have found an association of exposure to solid fuel smoke with COPD and chronic bronchitis, especially in women. 1,[17][18][19][20][21] In Sub-Saharan Africa, a study conducted by Fullerton in Malawi reported a COPD prevalence of 16%, higher than this study (1.6% among wood users). 10 The difference in results may be explained by the fact that the Malawian study included men and women whereas our study population comprised only women.…”
Section: Discussioncontrasting
confidence: 75%
“…Use of solid fuel was associated with higher risk for COPD. [11] From the present study we conclude that COPD although a smoker's disease is becoming common in women with passive smoking, and using kerosene stove and Biomass combustion as cooking medium in home due to smoke inhalation in the rural areas, although the disease was also present in the patients living in urban areas but the cause in them was cigarette smoking. Also the onset of the disease start earlier in women as compared to men as in our study most females were of younger age group.…”
Section: Discussionsupporting
confidence: 48%
“…About 7.5 meals per week were cooked outside. It is noteworthy that open-fire stoves pollute enough that they produce significant exposure even when used outdoors, and rates of COPD appear similar for those who cook inside or outside with open flame stoves (Balakrishnan et al 2002 andJohnson et al 2011).…”
Section: B Sample Statisticsmentioning
confidence: 99%